Surgery in the COVID-19 pandemic - Kumar, Satish; Pal, Sanjay; Kalyanasundar, Suresh (International Surgery Journal, 2020)
The world is going through a difficult time with the COVID-19 pandemic for the last five months and has affected more than 200 countries. Wuhan in China was the first place and then this has spread all over the globe. The virus affects the respiratory tract predominantly leading to death more so in the elderly and those with comorbid conditions. All routine and planned surgical services had to be stopped in view of the very rapid spread of the virus compounded by the lack of a proper treatment. It has been nearly 90 days and surgical services need to restart. There are various protocols being practiced and we have also put up a protocol which is simple and wherein the disease has been triaged into three groups and accordingly treatment is executed. All surgical emergencies are treated considering them as COVID positive till proved by a negative test.